Persepsi Masyarakat Terhadap Pelayanan Akta Kelahiran Berbasis Online di Dinas Kependudukan dan Pencatatan Sipil Kota Samarinda - Diah Ayu Pitaloka; Letizia Dyastari; Melati Dama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The problem in this study is how the Lempake Village community views online-based birth certificate services.This type of research is qualitative research with a descriptive statistical approach that aims to provide a description of the phenomenon under study. The data analysis technique uses a frequency distribution analysis technique, which is an analytical technique that produces descriptive data which is percentaged to produce valid concluding data. The sampling technique used in this study was accidental sampling and snowball sampling with a research focus on public perception indicators in the form of: Service Procedures, Completion Time, Service Fees, Service Products and Service Supporting Facilities and Infrastructure. The results of this study indicate that the service procedures that have been determined according to the Lempake Village community through the official website sarpras are easy with a percentage of 86.73%. Via e-mail 2.04% think it's easy. While the service procedure via whatsapp, 81.63% thought it was easy. The service time that has been set is in accordance with the provisions that have been set with a percentage of 79.59%. The service fee specified in the online-based birth certificate service is in accordance with the provisions with a percentage of 77.56%. The service products that have been produced have good quality in terms of pronunciation to service product materials with a percentage of 90.81%. 9.19% there are still errors. Supporting infrastructure for online-based birth certificate services is easy with a percentage of 77.54%.